Senior digital exclusion: life stories, generations and generational culture - Rebelo, Catarina (2016)
The digital divide based on age is one of the main forms of digital exclusion within societies. In an increasingly aging society which is also increasingly mediated by technology it poses serious challenges both for excluded individuals and for the societies they integrate. It is important to better understand this phenomenon whose study, however, presents important challenges. One of the main challenges of studying the relationship of the older adults with the Internet is that the elderly are a highly heterogeneous group. This article is devoted to, for one hand, reflect on the issue of senior digital divide and, on the other hand, on the specific challenges of its study and how the concepts of generation and generational culture,along with the methodological approach of life stories,can contribute to better address this challenge.